Penerapan model pembelajaran berbasis proyek untuk meningkatkan penguasaan konsep dan mengetahui profil keterampilan proses sains siswa sma - Fitriani, Dian Nonik; Ramalis, Taufik Ramlan; Ayubi, Yuyu Rachmat (Universitas Pendidikan Indonesia (UPI), 2013)
KTSP curriculum and 2013 curriculum both of them are demanding world education are able to develop all of the potential of their students through the science process skills optimally in each learning activity. It aims that students have quality and competence to compete in this age of globalization. The purpose of this research is to improve the student's mastery of the concept after implementing a model project-based learning and knowing the science process skills profile during the process of project-based learning. The research method used was Pre-Experiment with one group pretest-posttest design. The subject of the research was 41 grade X-MIA-1 in one of senior high school in Cirebon Regency. The research was carried out as many as three times. Increased mastery of the concepts obtained from normalization gain the result of pre- test and post-test. Science process skills profiles obtained from the results of the assessment of student's performance observation sheets that contain KPS aspects at the meeting first, second and third. The results showed that the values of the normalized gain mastery of 0.59 with medium category. Science process skills profile of the students from the first to the third meeting changes, with an average percentage amounted to 66,4% with